Cryo-EM structure of human Pol κ bound to DNA and mono-ubiquitylated PCNA - Lancey, Claudia; Tehseen, Muhammad; Bakshi, Souvika; Percival, Matthew; Takahashi, Masateru; Sobhy, Mohamed A.; Raducanu, Vlad S.; Blair, Kerry; Muskett, Frederick W.; Ragan, Timothy J.; Crehuet, Ramon; Hamdan, Samir M.; et al. (Nature communications, 2021)
Y-family DNA polymerase κ (Pol κ) can replicate damaged DNA templates to rescue stalled replication forks. Access of Pol κ to DNA damage sites is facilitated by its interaction with the processivity clamp PCNA and is regulated by PCNA mono-ubiquitylation. Here, we present cryo-EM reconstructions of human Pol κ bound to DNA, an incoming nucleotide, and wild type or mono-ubiquitylated PCNA (Ub-PCNA). In both reconstructions, the internal PIP-box adjacent to the Pol κ Polymerase-Associated Domain (PAD) docks the catalytic core to one PCNA protomer in an angled orientation, bending the DNA exiting the Pol κ active site through PCNA, while Pol κ C-terminal domain containing two Ubiquitin Binding Zinc Fingers (UBZs) is invisible, in agreement with disorder predictions. The ubiquitin moieties are partly flexible and extend radially away from PCNA, with the ubiquitin at the Pol κ-bound protomer appearing more rigid. Activity assays suggest that, when the internal PIP-box interaction is lost, Pol κ is retained on DNA by a secondary interaction between the UBZs and the ubiquitins flexibly conjugated to PCNA. Our data provide a structural basis for the recruitment of a Y-family TLS polymerase to sites of DNA damage. Translesion Synthesis is a process that enables cells to overcome the deleterious effects of replication stalling caused by DNA lesions. Here the authors present a Cryo-EM structure of human Y-family DNA polymerase k (Pol k) bound to PCNA, P/T DNA and an incoming nucleotide; and propose a model for polymerase switching in which “carrier state” Pol k is recruited to PCNA.